Evaluating an Additional Measure for the American University of Sharjah English Placement Test: Using Analytical Scoring - John, Mary Anne (2009)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Mary Anne John Entitled, "Evaluating an Additional Measure for the American University of Sharjah English Placement Test: Using Analytical Scoring," June 2009. Available are both Hard and Soft Copies of the Thesis.